Heavy Ion Results from ATLAS - Onofre, A. (2017)
These proceedings provide an overview of the new results obtained with the ATLAS detector at the LHC, which were presented in the Quark Matter 2017 conference. These results were covered by twelve parallel talks, one flash talk and eleven posters. These proceedings group these results into five areas: initial state, jet quenching, quarkonium production, longitudinal flow dynamics, and collectivity in small systems.